Photocatalytic Degradation of Dissolved Organic Matter in the Ground Water Employing TiO2 Film Supported on Stainless Steel Plate - Andayani, Winarti; Sumartono, Agustin; Lindu, Muhammad (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
The Taman Palem Residences,Cengkareng, Indonesia has a groundwater problem as a main sources of drinking water in thearea due to yellowish brown colour of the water, that may come from dissolved organicmatter (DOM), humic substances. Photocatalytic degradation using TiO2 coated on a stainlesssteel plate (8 x 8 cm) to degrade the dissolved organic matter was studied.Groundwatersamples were collected at 150 m deep from Taman Palem Residences. The TiO2 catalyst wasmade from deep coating in a sol-gel system of titanium (IV) diisopropoxidebisacetylacetonate(TAA) precursor and immobilized at stainless steel plate (8 x 8 cm), followed by calcination at525oC. Two catalyst sheets were put in batch reactor containing groundwater. The groundwater containing DOM were irradiated by UV black light at varying initial pH values i.e 5, 7and 9. Sampling of solution was taken at the interval time of 0, 1, 2, 4, and 6 hours. DOMresidu in water before and after irradiation were measured by spectrophotometer UV-Vis at300 nm. Photocatalytic degradation of DOM was greater in acid solution than in basicsolution. The determination of intermediate degradation products by HPLC revealed thatoxalic acid was detected consistently.